(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines the issue of the dependence of the effectiveness of public services on public oversight. The importance of openness and transparency in the activities of public services in implementing public oversight is substantiated. The importance of arming civil society institutions with knowledge of oversight activities is shown in order to make public oversight effective.